(Studi pada Perusahaan Terdaftar di Bursa Efek Indonesia Tahun 2012) PRAKTIK PENGUNGKAPAN INFORMASI MODAL INTELEKTUAL - , YURIKA ANGGESTY, Syaiful Ali, S.E., M.I.S., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to examine the extents of intellectual capital disclosure of large listed firms in Indonesia by analysing the percentage of intelectual capital disclosure in annual report highlighting the differences in intellectual capital disclosure practice in the term of different size and different industry. Furthermore, this study analyze the effect of intellectual capital disclosure on the changes of stock prices. The paper begins by examining each of the top 50 firms by market capitalization listed on the Indonesia stock exchange in 2012. Using the content analysis method, it reviews the annual reports of these firms to determine the extents of intellectual capital items reported in Indonesia. It then determine the differences in intellectual capital disclosure practices between different size and different industry. Then, using multiple linier regression method, this study analyze the effect of intellectual capital disclosure on the changes of stock prices. The findings in this study highlight the need for a uniform intellectual capital disclosure and a reporting framework that provides comparative and consistent reporting under the auspices of a regulatory body. There are no significant effect in the changes of stock prices, it is argued that the changes of stock prices indicate response to financial information other than intellectual capital information. Intellectual capital disclosure differences were identified between different size of the firms because of different pressure the firms had, but there are no significant differences between different industry of the firms because the barrier to competition is slowly fading. This paper highlights important policy issues for Indonesia and other nations. These issues are even more pertinent due to globalization and access to capital market. Most study on intellectual capital disclosure have focused on extents of intellectual capital disclosure. This study offers insights into the effects of intellectual capital disclosure to investor.